Intensive Survey Data from Antikythera, Greece. (15th February 2012) - Bevan, Andrew; Conolly, James
The Antikythera Survey Project was an interdisciplinary programme of fieldwork, artefact study and laboratory analysis that considered the long-term history and human ecology of the small Greek island of Antikythera. It was co-directed by Andrew Bevan (UCL) and James Conolly (Trent), in collaboration with Aris Tsaravopoulos (Greek Archaeological Service), and under the aegis of the Canadian Institute in Greece and the Hellenic Ministry of Culture. Its various primary datasets are unusual, both in the Mediterranean and beyond, for providing intensive survey coverage of an entire island's surface archaeology.